2015
DOI: 10.1148/radiol.14132607
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Quantification of Airway Inflammation Following Segmental Allergen Challenge with Functional MR Imaging: A Proof of Concept Study

Abstract: OTF oxygen transfer function and volume over threshold are noninvasive MR imaging-derived parameters to visualize and quantify the regional allergic reaction after segmental endobronchial allergen challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
(39 reference statements)
1
11
0
1
Order By: Relevance
“…Therefore, MRI techniques are emerging that use short echo time sequences in conjunction with oxygen shortening lung tissue T1 to provide a surrogate of regional ventilation (9). Although the oxygen-enhancement signal depends on more than regional ventilation, it has been shown to significantly correlate with PFT measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MRI techniques are emerging that use short echo time sequences in conjunction with oxygen shortening lung tissue T1 to provide a surrogate of regional ventilation (9). Although the oxygen-enhancement signal depends on more than regional ventilation, it has been shown to significantly correlate with PFT measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in studies of lung volume reduction surgery candidates and asthma patients, OE MRI showed equal or superior performance in detecting treatment effect and disease severity compared with PFT, CT, and/or nuclear medicine study. More recently the OTF was shown to decrease in asthmatics after allergen challenge and correlated with the percentage of eosinophils in bronchoalveolar lavage at the site of challenge …”
Section: Applicationsmentioning
confidence: 99%
“…MRI was increasingly applied also in patients with asthma, demonstrating the occurrence of segmental lung edema and being a robust method for monitoring the response to treatment. [164][165][166][167]. Furthermore, it has been shown that hyperpolarized gases allow the evaluation of functional changes in distal small airways of asthmatic patients.…”
Section: Magnetic Resonance Imaging (Mri) and Pet/mrimentioning
confidence: 99%